Impacts of Climate Change on Youth’s Place Attachment: A Case Study of Tasiilaq, East Greenland - Risager Nielsen, Maria; Leppert, Marie-Louise; Becker Jacobsen, Rikke (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
This article examines the impacts of climate change on youth’s place attachment and highlights the pressing need to understand its implications for urban space utilization in the rapidly changing Arctic. The study employs an expanded place attachment theory, considers the influencing factor of climate change, and adopts a decolonization of science as well as a community-based participatory research approach to investigate Tasiilaq youth’s perspectives on their attachment to public spaces. The findings show that place attachment for these youth is shaped by the fulfillment of functional and emotional needs, encompassing social interaction, physical activity, and reflective purposes. The study concludes that climate change affects the place attachment of these youth in a multifaceted manner influenced by a complex interplay of factors. Results also reveal potentially positive and negative effects of climate change on place attachment, mediated by the youth’s functional and emotional needs and availability of alternative places.